Most-liked and least-liked television personalities as perceived by selected students of the Araullo High School implications to education - Chaiyadej, Patcharintara 1948
The primary purpose of this study was to look into the perceptions of randomly chosen high school students about their most-liked and least-liked television personality. Specifically the paper sought to determine who among the television personalities high school students like most or like least and how the students describe these personalilties.